2012
DOI: 10.1155/2012/203768
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Invasion Risk ofEucalyptusin the United States Using the Australian Weed Risk Assessment

Abstract: Many agricultural species have undergone selection for traits that are consistent with those that increase the probability that a species will become invasive. However, the risk of invasion may be accurately predicted for the majority of plant species tested using the Australian Weed Risk Assessment (WRA). This system has been tested in multiple climates and geographies and, on average, correctly identifies 90% of the major plant invaders as having high invasion risk, and 70% of the noninvaders as having low r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 37 publications
0
33
0
3
Order By: Relevance
“…Conversely, we could find no records of invasions from tropical plantations of Eucalyptus species or of the widely planted teak, Tectona grandis. It has been suggested that Eucalyptus species are non-invasive because the seeds are of low viability and poorly dispersed [53][54][55], but in such a large and diverse genus it seems unlikely that all species suffer from the same limitations. Given the recent massive expansion of pulpwood plantations in the tropics, and the planned expansion of biofuel crops, it is likely that there is a large "invasion debt" that will be realized over the next few decades [43].…”
Section: Plantation Forests As Source Of Invasionmentioning
confidence: 99%
“…Conversely, we could find no records of invasions from tropical plantations of Eucalyptus species or of the widely planted teak, Tectona grandis. It has been suggested that Eucalyptus species are non-invasive because the seeds are of low viability and poorly dispersed [53][54][55], but in such a large and diverse genus it seems unlikely that all species suffer from the same limitations. Given the recent massive expansion of pulpwood plantations in the tropics, and the planned expansion of biofuel crops, it is likely that there is a large "invasion debt" that will be realized over the next few decades [43].…”
Section: Plantation Forests As Source Of Invasionmentioning
confidence: 99%
“…Eucalyptus characteristics that may increase its potential invasiveness include rapid growth and maturation, adaptation to poor soil and variable conditions, evergreen character with no dormant period, high seed production, and dispersal of seeds via water [27][28][29]. However, field evidence suggests Eucalyptus species in general have been much slower to invade than would be predicted by their rapid growth and climate tolerance.…”
Section: Invasivenessmentioning
confidence: 99%
“…This evidence includes a general lack of success as invaders in most circumstances, very slow rates of spread in its native range, and frequent observations of high mortality following seeding and planting [27,[30][31][32]. Characteristics of Eucalyptus seeds, including the lack of dispersion through wind or animal vectors and protective capsules that reduce seed release in the absence of fire, likely reduce the risk of significant invasion [27,28]. Studies in Australia and South Africa have also shown that most seeds fall in close proximity to parent trees, limiting its potential spread [27,29,33].…”
Section: Invasivenessmentioning
confidence: 99%
“…But there are also several studies that have contributed to appropriate environmental management of eucalypts stands. The studies are related to invasiveness (Silva et al, 2011;Gordon et al, 2012), flammability (Gill and Zylstra, 2005), nutrient cycling (Laclau et al, 2005) and water consumption (Lima et al, 1990;Almeida and Soares, 2003).…”
Section: Introductionmentioning
confidence: 99%